Overview of the efficiency of using the triage Emergency Severity Index (ESI) in emergency installations: A systematic review - Tezar Nusi; Yulian Lestari; Suryanto Suryanto (Universitas Aisyah Pringsewu, 2023)
Introduction The Emergency Room (IGD) is unique in operation compared to units or installations from all parts of the hospital, because the Emergency Room operates around the clock with the presence of patients in an emergency and unscheduled state as well as a high flow of patients in and out. The patient is in a critical condition requiring immediate life-saving intervention until the patient is in a relatively stable condition. The Emergency Severity Index (ESI) is a triage system that categorizes 5 levels of severity, levels 1-2 require immediate treatment while levels 3-5 determine how many resources the patient needs. Inclusion of resource requirements in determining triage levels is a unique feature of the ESI triage system. Method The author uses the method used to conduct a systematic review is to search through the internet. Literature search used PubMed, google scholar, and Science Direct with keywords in English: Emergency Severity Index (ESI), Emergency Department. Inclusion criteria in this study were articles discussing the Efficiency of Using the Emergency Severity index, articles in English and Indonesian, limitations of articles published in the last 5 years (2018-2023) discussing the efficiency of using ESI, and full text articles, Exclusion criteria and criteria abstract only exclusions, articles with the type of review . The results of the literature search results obtained as many as 16 journal articles that are relevant to the research objectives. Conclusion emergency severity index (ESI) can be applied in emergency departments with a high level of sensitivity, specificity, accuracy and triage decisions. ESI can be modified with other methods and works well. ESI can also be used in vulnerable groups such as the elderly, children - post partum children and mothers. Suggestion Emergency severity index can be a reference to be applied in emergency departments in Indonesia because it has high efficiency. Abstrak: Introduction Instalasi Gawat Darurat (IGD) unik dalam pengoperasian dibandingkan dengan unit atau instalasi dari seluruh bagian rumah sakit, karena IGD beroperasi sepanjang waktu dengan kehadiran pasien dalam keadaan gawat darurat dan tidak terjadwal juga alur masuk keluar pasien yang tinggi. Pasien dalam kondisi kritis yang membutuhkan intervensi penyelamatan hidup segera sampai pasien pada kondisi relatif stabil. Emergency Severity Index (ESI) adalah sistem triase yang mengkategorikan 5 level keparahan, level 1 – 2 membutuhkan penanganan segera sedangkan level 3-5 menentukannya dengan berapa banyak sumber daya yang dibutuhkan pasien. Pencantuman kebutuhan sumber daya dalam penentuan tingkat triase adalah fitur unik dari sistem triase ESI. Method Penulis menggunakan metode yang digunakan untuk melakukan sebuah systematic review adalah dengan mencari melalui internet. Pencarian literatur menggunakan PubMed, google scholar, dan Science Direct dengan kata kunci dalam bahasa Inggris: Emergency Severity Index (ESI), Emergency Department. Kriteria inklusi dalam penelitian ini adalah artikel yang membahas Effisiensi Penggunaan Emergency Severity index, artikel di Bahasa Inggris dan Indonesia, batasan artikel yang diterbitkan di 5 tahun terakhir (2018-2023) membahas tentang effisiensi penggunaan ESI, dan artikel teks lengkap, kriteria Eksklusi dan kriteria eksklusi hanya abstrak, artikel dengan jenis review . Result hasil pencarian literature didapatkan jurnal sebanyak 16 artikel yang revelan dengan tujuan penelitian. Conclusion emergency severity index (ESI) bisa diterapkan di instalasi gawat darurat dengan tingkat sensifitas, spesifikasi, akurasi dan keputusan triase yang tinggi, ESI bisa dimodifikasi dengan metode lainnya dan dapat berjalan dengan baik, ESI juga bisa digunakan pada kelompok rentan seperti lansia, anak -anak dan ibu post partum. Suggestion Emergency severity index bisa menjadi salah satu referensi untuk diterapkan di instalasi gawat darurat di Indonesia karena memiliki effiensi yang tinggi.